Penerapan Algoritma K-Means Clustering Untuk Menentukan Kelas Kelompok Bimbingan Belajar Tambahan - Silvia Ningsih (Jurnal Sistem Informasi (JUSIN), 2022)
Additional learning is a learning program that is carried out outside the school's intracurricular program. This means that additional learning activities are carried out after the regular learning program at school has ended The learning mentor comes from the subject teacher at the school concerned. It is commonly called the afternoon additional learning program. The afternoon additional learning program has its own planning schedule. Additional learning is carried out by students to improve their understanding and deepening of subject material. This goal is related to the preparation of a student to face exams at school, both midterm exams, semester final exams and national final exams. In determining the class of this additional study group using the K-Means Clustering algorithm, the number of data samples will be used is 26 students majoring in science.